A feminilidade como identidade da mulher no conto "At the bay", de Katherine Mansfield - Farias, Larissa Bruna Batista de (2018)
This research looks into the characters from the short story "At the bay" (1922), by the New Zealander writer Katherine Mansfield, in a woman‘s identity perspective. In order to do it so, we are going to pass through discussions about women‘s condition in the early twentieth century, the identity crisis, and the author‘s life and her literary. After that, the characters Linda Burnell, Mrs. Fairfield, Beryl Fairfield, Mrs. Harry Kember, and Alice, who are part of the patriarchal English society, are going to be analyzed. In this way, we intend to motivate the reader to have a critical insight into Mansfield's writings and help him to understand the behavior and moral conventions imposed to women throughout history. As a theorethical support we base our research on studies by Cecil Zinani (2013) and Kathryn Woodward (2014) to discuss about identity constructions; Pierre Bourdieu (2017), John Stuart Mill (1859; 1869), and Betty Friedan (1963; 1983) to female condition; Anthony Giddens (1993), Peter Stearns (2010), Carole Pateman (1993), and Bertrand Russell (2015) to women‘s sexuality and marriage; and Elisabeth Badinter (1985; 2011) to motherhood. As a result, we noticed gender identity issues similar to those that concern us in the contemporary times.